Spatial inequalities and policies in South Africa: Place-based or people-centred?. (July 2018) - Todes, Alison; Turok, Ivan
Highlights: SA has shifted from spatial rebalancing policies to a mix of place based and space neutral approaches. There has been much experimentation without an overarching policy framework or vision. Both the space neutral and spatial rebalancing approaches are difficult to justify in SA. The structure and character of the economy are neglected in spatial policy debates. The social, political and institutional environment shapes prospects for spatial policies. Abstract: There is a robust international debate about how best to tackle spatial inequalities within nations and regions. The paper discusses three contrasting approaches: spatial rebalancing, space-neutral and place-based. They vary in the scope and purpose of government policy, from redistributing economic activity, to facilitating aggregate growth, and realising the economic potential of less-developed regions. The paper applies this framework to analyse South Africa's five decades of experience of spatial policies. The context is one of stark spatial inequalities, uneven institutional capabilities, and mounting political pressure for change. Under apartheid, spatial targeting was highly instrumental and played a role in reproducing social divisions at considerable financial cost. Since the end of apartheid there has been much experimentation with spatial initiatives, but without any overarching vision or policy framework. A cautionary conclusion is that there are risks of extravagant spending in marginal locations when political pressures are strong, public institutions are weak and economic disciplines are lacking. Another is that place-based policies have potential, but require stronger vertical and horizontal policy alignment to stand any chance of tackling entrenched spatial divides. Enhanced local institutions involving private sector and community stakeholders are also essential for spatial policies to respond to the specific challenges and opportunities encountered in each place.